Małżeństwa mieszane i jak sobie w nich radzić według „tablicy małżeńskiej” 1P 3,1-7. Za czy przeciw tradycji Pawłowej? - Rambiert-Kwaśniewska, Anna (Collectanea Theologica, 2018)
When looked at from the modern reader’s perspective, the “Marriage Table”, which is one of the elements of the so-called Haustafeln (household codes), is a quite difficult passage. This is more so since there are a few of them in the New Testament (Eph 5,22-6,9; Col 3,18-4,1; Tit 2,1-10 and 1 Pet 2,13-3,7). The main difficulty that one encounters while reading them is that they stress a lower status of women, expressed in the idea of “subjection”. The “Marriage Table” in 1 Pet 3,1-7, which is examined in the article, adds two aspects to the aforementioned interpretational problem: the religious diversity of spouses (mixed marriages) and, following it, violence. Numerous preachers accept a literal interpretation of the text, arguing that a woman in a marriage with an aggressive husband should endure the violence. A contextual and intertextual reading, however, leads us to discover that the heroic act of sacrifice for the sake of the husband’s conversion is not obligatory, but should be treated as an act of free will. Therefore a woman’s voluntary submission as well as her being a victim of aggression for a greater good can subscribe to an idea of agape which Paul mentions in the “Marriage Table” of Eph 5,21-33.